Age Estimation Using Schour-Massler Method Compared to the Demirjian Method: Estimasi Usia Menggunakan Metode Schour-Massler Dibandingkan dengan Metode Demirjian - Boel, Trelia; Bahri, Tiara Ayustin (Dentika: Dental Journal, 2019)
Schour-Massler and Demirjian are methods used to estimate chronological age in dental radiographs by looking at the development of permanent teeth and the maturity of the dental age. Chronological age is based on date of birth. Dental age is the age based on the maturity of the teeth. Both of these methods have been widely used in previous studies, but have never been compared. The purpose of this study was to determine whether there are differences in age estimation using the Schour-Massler and Demirjian methods. This study was an observational analytic study with a cross sectional design. The research sample was 46 patients who came to USU General Hospital at the age of 10-16 years. This research was consist at the Radiology Unit of the Faculty of Dentistry, University of North Sumatra. The results of this study indicate the p value of the Wilcoxon test results with the p value for Schour-Massler p=0.090 > 0.05 and Demirjian p=1,000. Both p values> 0.05, there is no significant difference in assessing the estimated age using both methods, so Ha is accepted. In conclusion, the Schour-Massler and Demirjian methods provide estimates of age that are close to actual age, so there is no significant difference between the two methods.